Technology Acceptance Model (TAM) In The Use of Online Learning Applications During The Covid-19 Pandemic For Parents of Elementary School Students - Aulia Nuraini Kusumadewi; Nanda Anthony Lubis; Rhomy Prastiyo; Dewi Tamara (research, training and philanthropy institution Natural Aceh, 2021)
Abstract: School from Home is one of the Indonesian government's efforts to minimize the spread of the Covid-19. All teaching and learning activities have been transferred to various online learning applications, including elementary school students. The parents of these elementary school students have to operate multiple online learning applications so that their children can participate in distance learning activities. Researchers have already used the original Technology Acceptance Model (TAM) to determine the acceptance of online learning applications by parents of elementary school students as a means of distance learning. Researchers want to know the acceptance of online learning applications which are carried out in sudden conditions and without prior preparation but must be implemented. Researchers hope that the results of this study can capture the acceptance of parents of elementary students to School from Home during the Pandemic and can be used for evaluation and continuous improvement of the School from Home system. Referring to the literature with 22 questionnaire questions, the minimum number of respondents who must be obtained is 110 people, in this study 155 parents of elementary school students in Jabodetabek participated in filling out the questionnaire using an online questionnaire with a significance level of 5% and data processed using PLS-SEM 3.0 resulted in a strong relationship. There is no significant difference between Perceived Ease of Use and Attitude Toward Using. Then, a significant relationship was generated between Perceived Ease of Use on Perceived Usefulness, Perceived Usefulness on Attitude Toward Using, Perceived Usefulness on Behavioral Intention To Use, Attitude Toward Using on Behavioral Intention To Use. However, the results show a positive value Path Coefficient in Structural Model Result, so this research is consistent and according to TAM. Abstrak: School from Home menjadi salah satu upaya pemerintah Indonesia dalam mengurangi penyebaran virus Covid-19. Seluruh kegiatan belajar mengajar dialihkan dengan menggunakan berbagai aplikasi online learning, begitu pula dengan pendidikan untuk murid Sekolah Dasar. Para orang tua murid Sekolah Dasar ini, bagaimanapun juga harus mendampingi dan mengoperasikan berbagai aplikasi online learning agar putra putrinya dapat mengikuti kegiatan pembelajaran jarak jauh. Peneliti menggunakan Technology Acceptance Model (TAM) asli untuk mengetahui penerimaan aplikasi online learning oleh orang tua murid Sekolah Dasar ini sebagai sarana pembelajaran jarak jauh. Peneliti ingin mengetahui penerimaan aplikasi online learning yang dilaksanakan dalam kondisi mendadak dan tanpa persiapan sebelumnya namun harus dilaksanakan. Peneliti berharap hasil penelitian ini dapat menangkap penerimaan orang tua murid siswa SD terhadap School from Home selama Pandemi dan dapat digunakan untuk evaluasi maupun perbaikan berkelanjutan sistem School from Home. Mengacu pada literatur dengan 22 pertanyaan kuesioner, minimum responden yang harus didapatkan sebanyak 110 orang, dalam penelitian ini 155 orang tua murid SD di Jabodetabek berpartisipasi dalam pengisian kuesioner menggunakan online kuesioner dan tingkat signifikansi 5% dan data diolah menggunakan PLS-SEM 3.0 menghasilkan hubungan yang tidak signifikan antara Perceived Ease of Use terhadap Attitude Toward Using. Kemudian, dihasilkan hubungan yang signifikan antara Perceived Ease of Use terhadap Perceived Usefulness, Perceived Usefulness terhadap Attitude Toward Using, Perceived Usefulness terhadap Behavioral Intention To Use, Attitude Toward Using terhadap Behavioral Intention To Use. Namun, Hasil dari model penelitian ini tetap dikatakan konsisten dan sesuai dengan TAM, karena nilai Path Coefficient pada Structural Model Result yang dihasilkan seluruhnya bernilai positif.